The Influence of Corporate Governance and Covid-19 on Tax Avoidance in Mining Companies Listed on The IDX From 2018 to 2023 - Rifqoh Nailufar, Fairuz; Hamidi, Masyhuri; Fany Alfarisi, Mohamad (Journal of Accounting and Finance Management, 2024)
This study aims to analyze the effect of corporate governance, share ownership, management compensation, and the Covid-19 pandemic on tax avoidance in mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2023. Corporate governance is measured by the number of independent commissioners and audit committees, while share ownership includes institutional and managerial ownership. This study uses 20 companies as samples with a total of 120 data observations using the purposive sampling method. The research data were analyzed using panel data regression using EViews12 software. The number of independent commissioners and institutional ownership contribute to a decrease in tax avoidance by increasing supervision and compliance. Conversely, the number of audit committees and management compensation are positively related to tax avoidance, indicating weaknesses in the effectiveness of supervision and compensation incentives that encourage tax avoidance. Managerial ownership has a negative but insignificant effect on tax avoidance. The Covid-19 pandemic shows a positive but insignificant effect, with government policies and corporate governance helping to limit its impact. Overall, the low tax ratio in the mining sector could be related to a combination of these factors, including weaknesses in corporate governance, audit committee effectiveness, institutional ownership, and inadequate compensation incentives. This study also found that the low tax ratio in the mining sector is closely related to tax avoidance practices carried out by companies. The implications of this study are the importance of increasing supervision of corporate governance, especially in terms of the effectiveness of independent commissioners and audit committees, as well as transparency in share ownership and management compensation. Government policies and related authorities need to be strengthened to minimize tax avoidance practices, in order to increase state tax revenues from the mining sector.